The Interplay between Public and Private Information in Asset Markets: Theoretical and Experimental Approaches - Simone Alfarano; Eva Camacho; Marko Petrovic; Giulia Provenzano (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2014)
In this paper we will give an overview of the more relevant results on the theoretical and experimental research related to public and private information dissemination and aggregation in asset markets, focusing mainly on the contemporaneous presence of public and private information and its effect on market performance. We conclude that the theoretical literature is more developed than the experimental one when dealing with public information and its role in different economic environments. Therefore, a promising research avenue opens for experimentally testing the different, and often contradictory, theoretical results.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C92; D82; G14; 330; experiments; financial markets; private and public information; central bank information